THE EFFECT OF GUIDED INQUIRY LEARNING MODELS ON STUDENT LEARNING OUTCOMES IN EXCRETORY SYSTEM MATERIALS - Cut Ratna Dewi; Nurmuna Saputri; Eriawati Eriawati (Jurnal Biologi Sains dan Kependidikan, 2021)
The learning process in the classroom is very influential on student achievement. So far, the achievement of student learning outcomes is still not optimal, especially in complex materials such as the excretory system. This study was conducted to determine the effect of the application of the guided inquiry model on student learning outcomes on the excretory system material at SMA Negeri 1 Peulimbang. This study used a pre-experimental design with a one-group pretest-posttest design. The population in this study were all students of class XI science. While the samples were students of class XI IPA 2, totaling 20 people. The sampling technique used purposive sampling. Collecting data using test techniques, namely pre-test and post-test. Data were analyzed using a t-test statistic. The results of the study obtained the value of t-count = 6.52 and t-table = 0.95 at a significant level of 0.05 and dk = n-1. This shows that t-count (6.52) t-table (0.95) so that Ha is accepted and H0 is rejected. So it can be concluded that the guided inquiry learning model has a significant effect on improving student learning outcomes on the excretory system material.Keywords: Guided Inquiry, Excretory System, Student Learning Outcomes